Package material, package bag and package

The packaging material, featuring a heat-resistant coating layer, polyethylene substrate, adhesive layer, and polyethylene sealant layer, addresses the challenges of thin film thickness, mechanical properties, recyclability, and bag production, achieving efficient and environmentally friendly packaging solutions.

JP2025060217APending Publication Date: 2025-04-10DAI NIPPON PRINTING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023170803
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing packaging materials face challenges in achieving a balance between thin film thickness, excellent mechanical properties, high recyclability, and suitable bag production processes, particularly due to issues with film wrinkling, increased plastic usage, and reduced recyclability.

Method used

A packaging material structure comprising a heat-resistant coating layer, a substrate with polyethylene as the main component, an adhesive layer, and a sealant layer with polyethylene as the main component, all in a specific order, with a total thickness of 150 μm or less.

Benefits of technology

This configuration enables the production of packaging materials with thin film thickness, enhanced mechanical properties, improved recyclability, and increased productivity, while reducing plastic usage and environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060217000001_ABST
    Figure 2025060217000001_ABST
Patent Text Reader

Abstract

To provide a package bag which has a thin thickness, yet exhibits excellent mechanical physical properties and recyclability, and also demonstrates an excellent bag making property.SOLUTION: A package material includes at least: a heat proof coat layer; a base material; an adhesive layer; and a sealant layer in this order. The base material is mainly composed of polyethylene and the sealant layer is mainly composed of polyethylene. The package material has a total thickness of 150 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to packaging materials, packaging bags and packages. [Background technology]

[0002] Packaging bags are used to store industrial materials (for example, Patent Document 1). Industrial materials usually have an uneven shape. For this reason, it is desirable for the packaging bags that store industrial materials to have excellent mechanical properties. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2022-122294 Summary of the Invention [Problem to be solved by the invention]

[0004] When making a packaging bag using only a single-layer polyethylene film, it is necessary to increase the resin density and the film thickness in order to improve the mechanical properties. However, when making a film using polyethylene with a high resin density, the thicker the film is, the more likely it is that wrinkles will occur in the film. In this case, for example, it is necessary to use a film-making machine dedicated to high-density resins. In addition, the thicker the film is, the more problems there are in terms of the amount of plastic used and the volume occupied.

[0005] In addition, by producing a packaging bag using a polyester film as a substrate and a polyethylene film as a sealant layer, the mechanical properties are improved even if the film thickness is small. However, on the other hand, there is a problem that the recyclability of the packaging bag is reduced. In recent years, attention has been paid to efforts to environmental problems such as plastic marine pollution and global warming. From the viewpoint of reducing the environmental load, there is a demand for recycling packaging bags.

[0006] Therefore, by producing a packaging bag using a polyethylene film that also serves as a base material and a sealing layer, the recyclability of the packaging bag is improved. However, on the other hand, there is a problem that heat sealing takes time due to the low heat resistance of the base material, and in order to improve mechanical properties, it is necessary to increase the thickness, and from the viewpoint of improving productivity, it is required to have excellent bag-making suitability.

[0007] An object of the present disclosure is to provide a packaging material that has excellent mechanical properties and recyclability despite its thin film thickness, and also has excellent suitability for bag formation. [Means for solving the problem]

[0008] The packaging material of the present disclosure comprises at least a heat-resistant coating layer, a substrate, an adhesive layer, and a sealant layer, in this order, the substrate containing polyethylene as a main component, the sealant layer containing polyethylene as a main component, and the packaging material has a total thickness of 150 μm or less. Effect of the Invention

[0009] According to the present disclosure, a packaging material can be provided that has excellent mechanical properties and recyclability despite its thin film thickness, and is also excellent in bag-making suitability. For example, by laminating two or more polyethylene films together, a packaging material can be produced that has excellent mechanical properties and can be sealed without being limited by the sealing method for bag making, even though the film thickness is thin. This also reduces the amount of plastic used. Since both the substrate and the sealant layer contain polyethylene as the main component, the packaging material is also excellent in recyclability. Furthermore, by providing a heat-resistant coating layer on one side of the substrate, heat sealing can be performed at a high temperature, and the time required for heat sealing can be shortened. This improves productivity and provides excellent bag-making suitability. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of one embodiment of a packaging material of the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view of one embodiment of a packaging material of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments of the present disclosure will be described in detail. The present disclosure can be implemented in many different forms, and is not to be interpreted as being limited to the description of the embodiments exemplified below. In the drawings, the width, thickness, shape, etc. of each layer may be shown diagrammatically in order to make the explanation clearer, but these are merely examples and do not limit the interpretation of the present disclosure. In this specification and each figure, elements similar to those already explained with respect to the previous figures are given the same reference numerals, and detailed explanations may be omitted as appropriate.

[0012] In the present disclosure, when multiple upper limit candidates and multiple lower limit candidates are listed for a certain parameter, the numerical range of the parameter may be configured by combining any one upper limit candidate and any one lower limit candidate. Examples of the above parameters include physical property values, component content ratios, and layer thicknesses. As an example, the description "Parameter B is preferably A1 or more, more preferably A2 or more, and even more preferably A3 or more. Parameter B is preferably A4 or less, more preferably A5 or less, and even more preferably A6 or less." will be explained. In this example, the numerical range of parameter B may be A1 or more and A4 or less, A1 or more and A5 or less, A1 or more and A6 or less, A2 or more and A4 or less, A2 or more and A5 or less, A2 or more and A6 or less, A3 or more and A4 or less, A3 or more and A5 or less, or A3 or more and A6 or less.

[0013] In this specification, each of the components (for example, polyolefins such as polyethylene, α-olefins, resin materials such as gas barrier resins, and additives) appearing in the following description may be used either alone or in combination of two or more kinds.

[0014] In this specification, polyethylene refers to a polymer in which the content of ethylene-derived structural units in all repeating structural units exceeds 50 mol%. In this polymer, the content of ethylene-derived structural units is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and particularly preferably 95 mol% or more. The content can be measured by NMR.

[0015] In this specification, polyethylene may be a homopolymer of ethylene, or a copolymer of ethylene and an ethylenically unsaturated monomer other than ethylene. Examples of the ethylenically unsaturated monomer other than ethylene include α-olefins having 3 to 20 carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene, vinyl monomers such as vinyl acetate and vinyl propionate, and (meth)acrylic acid esters such as methyl (meth)acrylate and ethyl (meth)acrylate.

[0016] In this specification, polyethylene includes, for example, high density polyethylene, medium density polyethylene, low density polyethylene and linear low density polyethylene, as well as ethylene-vinyl acetate copolymer and ethylene-(meth)acrylic acid ester copolymer.

[0017] In this specification, the density of polyethylene is as follows: The density of the high density polyethylene is preferably 0.945 g / cm 3 The density of the high density polyethylene is preferably greater than 0.965 g / cm 3 The density of the medium density polyethylene is preferably 0.928 g / cm 3 Exceeds 0.945g / cm 3 The density of the low density polyethylene is preferably 0.860 g / cm 3 More than 0.928g / cm 3Less than or equal to 0.900 g / cm 3 More than 0.928g / cm 3 The density of the linear low density polyethylene is preferably 0.860 g / cm 3 More than 0.928g / cm 3 Less than or equal to 0.900 g / cm 3 More than 0.928g / cm 3 In this specification, the density of polyethylene is measured in accordance with JIS K7112:1999, Method D (density gradient tube method, 23° C.).

[0018] Low-density polyethylene is, for example, polyethylene obtained by polymerizing ethylene by high-pressure polymerization (high-pressure low-density polyethylene). Linear low-density polyethylene is, for example, polyethylene obtained by polymerizing ethylene and a small amount of α-olefins by a polymerization method using a multi-site catalyst such as a Ziegler-Natta catalyst or a single-site catalyst such as a metallocene catalyst.

[0019] Polyethylenes with different densities or branches can be obtained by appropriately selecting a polymerization method. For example, it is preferable to carry out polymerization in one or more stages by using a multi-site catalyst such as a Ziegler-Natta catalyst or a single-site catalyst such as a metallocene catalyst as a polymerization catalyst, by any of gas phase polymerization, slurry polymerization, solution polymerization, and high pressure ion polymerization.

[0020] In this specification, polyethylene may be polyethylene derived from biomass (hereinafter also referred to as "biomass polyethylene"). That is, as a raw material for obtaining polyethylene, ethylene derived from biomass may be used instead of ethylene obtained from fossil fuels. Since biomass polyethylene is a carbon-neutral material, it is possible to reduce the environmental load caused by the laminate or packaging bag. Biomass polyethylene can be produced, for example, by the method described in JP 2013-177531 A. Commercially available biomass polyethylene may be used.

[0021] As the polyethylene, mechanically recycled or chemically recycled polyethylene (hereinafter also referred to as "recycled polyethylene") may be used. This can reduce the environmental impact of the laminate or packaging bag. Mechanical recycling is generally a method in which recovered polyethylene films, etc. are crushed, washed with an alkali to remove dirt and foreign matter from the film surface, and then dried at high temperature and reduced pressure for a certain period of time to diffuse contaminants remaining inside the film, decontaminating it, removing the dirt from the film, and returning it to polyethylene. Chemical recycling is generally a method in which recovered polyethylene films, etc. are decomposed to the monomer level, and the monomers are polymerized again to obtain polyethylene.

[0022] In this specification, the "main component" of a substrate or layer refers to a component whose content in the substrate or layer is more than 50% by mass, preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more.

[0023] [Packaging materials] The packaging material of the present disclosure is a laminate comprising at least a heat-resistant coating layer, a substrate, an adhesive layer, and a sealant layer in this order. In the following description, the packaging material of the present disclosure is also referred to as the "laminate of the present disclosure". A laminate of this configuration, particularly a laminate formed by bonding a substrate and a sealant film, is excellent in mechanical properties such as puncture strength and tensile strength even when the total thickness is small. In addition, a laminate having a heat-resistant coating layer provided on one side of a substrate can be heat-sealed at high temperatures even when the heat resistance temperature of the substrate is insufficient, and is excellent in bag-making suitability.

[0024] The substrate contains polyethylene as a main component. The sealant layer contains polyethylene as a main component. The polyethylene contained in the substrate may be the same as or different from the polyethylene contained in the sealant layer.

[0025] In the laminate of the present disclosure, the substrate and the sealant layer each contain the same type of resin material, polyethylene, as a main component. By using a laminate having such a configuration, for example, a packaging bag with excellent recyclability can be produced.

[0026] 1 and 2 show schematic cross-sectional views of an embodiment of a laminate of the present disclosure. The laminate 1 of Fig. 1 includes a heat-resistant coating layer 40, a substrate 10, an adhesive layer 20, and a sealant layer 30 in this order in the thickness direction. The laminate 1 of Fig. 2 includes a heat-resistant coating layer 40, a substrate 10, an anchor coating layer 50, an adhesive layer 20, and a sealant layer 30 in this order in the thickness direction.

[0027] The content of polyethylene in the entire laminate of the present disclosure is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more. A mono-material packaging bag can be produced using such a laminate, and the recyclability of the packaging bag can be improved. The upper limit of the content of polyethylene is not particularly limited, but may be 99% by mass.

[0028] The total thickness of the laminate of the present disclosure is preferably 150 μm or less, more preferably 145 μm or less, even more preferably 140 μm or less, and even more preferably 135 μm or less, from the viewpoint of reducing the amount of polyethylene used and the volume of the packaging bag. The total thickness of the laminate of the present disclosure is preferably 20 μm or more, more preferably 40 μm or more, even more preferably 60 μm or more, even more preferably 80 μm or more, and particularly preferably 90 μm or more, from the viewpoint of the strength and heat resistance of the laminate.

[0029] <Base material> The laminate of the present disclosure includes a substrate. The substrate contains polyethylene as a main component. The polyethylene contained in the substrate is preferably high-density polyethylene, medium-density polyethylene, low-density polyethylene, or linear low-density polyethylene, and from the viewpoint of the strength and heat resistance of the substrate, high-density polyethylene and medium-density polyethylene are more preferable.

[0030] The melt flow rate (MFR) of the polyethylene contained in the substrate is preferably 0.1 g / 10 min or more, more preferably 0.2 g / 10 min or more, even more preferably 0.3 g / 10 min or more, and particularly preferably 0.5 g / 10 min or more, from the viewpoint of film-forming and processability. The MFR of the polyethylene is preferably 30 g / 10 min or less, more preferably 20 g / 10 min or less, even more preferably 10 g / 10 min or less, and particularly preferably 5 g / 10 min or less, from the viewpoint of film-forming and processability. In this specification, the MFR of the polyethylene is measured by the A method at a temperature of 190 ° C. and a load of 2.16 kg in accordance with JIS K7210-1:2014.

[0031] From the viewpoint of heat resistance, the melting point (Tm) of the polyethylene contained in the substrate is preferably 100° C. or higher, more preferably 105° C. or higher, even more preferably 110° C. or higher, particularly preferably 120° C. or higher, and preferably 140° C. or lower. In this specification, the Tm of various materials is the melting peak temperature obtained by differential scanning calorimetry (DSC) in accordance with JIS K7121:2012.

[0032] The content of polyethylene in the substrate is preferably 80% by mass or more, more preferably 85% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass or more. A laminate including such a substrate has excellent recyclability.

[0033] The substrate may contain a resin material other than polyethylene, for example, polyolefins such as polypropylene, polyamides, polyesters, (meth)acrylic resins, vinyl resins, cellulose resins, and ionomer resins.

[0034] The substrate may contain additives, such as crosslinkers, antiblocking agents, slip agents, antioxidants, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, dyes, and modifying resins.

[0035] The substrate may be a stretched substrate or a non-stretched substrate, but a stretched substrate is preferred. A stretched substrate means a substrate that has been subjected to a stretching treatment. A stretched substrate has, for example, excellent heat resistance and strength, and a high yield stress, which will be described later. Such a stretched substrate can fully satisfy the physical properties required, for example, as the outer layer of a packaging material.

[0036] The stretching process may be uniaxial stretching or biaxial stretching. The stretching ratio in the longitudinal direction (the lengthwise direction of the substrate, MD direction) is preferably 2 times or more, more preferably 3 times or more, and preferably 10 times or less, more preferably 7 times or less. The stretching ratio in the transverse direction (the direction perpendicular to the MD direction, TD direction) is preferably 2 times or more, more preferably 3 times or more, and preferably 10 times or less, more preferably 7 times or less. The stretched substrate is, for example, a uniaxially stretched substrate, specifically, a substrate uniaxially stretched in the MD direction (MDO substrate). When the stretching ratio is 2 times or more, for example, the rigidity, strength and heat resistance of the substrate can be improved, the printability of the substrate can be improved, and the transparency of the substrate can be improved. When the stretching ratio is 10 times or less, for example, good stretching can be performed without causing breakage of the film.

[0037] The substrate may have a single layer structure or a multilayer structure. Hereinafter, the substrate having a multilayer structure is also referred to as a "multilayer substrate". The multilayer substrate is excellent in strength, rigidity and heat resistance. The number of layers of the stretched substrate is preferably 2 or more, more preferably 3 or more, and is preferably 7 or less, more preferably 5 or less.

[0038] The substrate comprises a polyethylene layer. The substrate may be composed of a polyethylene layer, or may include a polyethylene layer and a barrier resin layer. The substrate may further include an adhesive resin layer between the polyethylene layer and the barrier resin layer. The substrate may include two or more polyethylene layers. The substrate may include two or more barrier resin layers. The substrate may include two or more adhesive resin layers.

[0039] The thickness of the substrate is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and is preferably 200 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, and particularly preferably 40 μm or less. Substrates having a thickness equal to or greater than the lower limit are excellent in, for example, strength, rigidity, and heat resistance. Substrates having a thickness equal to or less than the upper limit are excellent in, for example, processability.

[0040] The substrate can be prepared, for example, by forming a film from a material, and then stretching the film as desired. Examples of the film-forming method include inflation molding and T-die molding. According to the inflation molding method, stretching can be performed after film formation.

[0041] The substrate, in one embodiment, is a coextruded resin film. In one embodiment, the substrate is a resin film obtained by coextrusion film formation of materials constituting two or more polyethylene layers by a coextrusion inflation molding method or the like, and further stretching the obtained film.

[0042] In one embodiment, the substrate is a resin film obtained by co-extrusion film formation using a material constituting the polyethylene layer, and, if the substrate has an adhesive resin layer, a material constituting the adhesive resin layer, and a material constituting the barrier resin layer, by a co-extrusion inflation molding method or the like, and further stretching the obtained film.

[0043] The substrate may be surface-treated. Such a substrate has, for example, excellent adhesion to other layers. Examples of the surface treatment method include physical treatment and chemical treatment. Examples of the physical treatment include corona treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment. Examples of the chemical treatment include oxidation treatment using chemicals.

[0044] The yield stress of the substrate is preferably 50 MPa or more, more preferably 80 MPa or more, even more preferably 110 MPa or more, even more preferably 150 MPa or more, and particularly preferably 180 MPa or more. The present inventors have found that a laminate having a substrate with a yield stress of the above lower limit or more is suitable as a packaging material for industrial materials, particularly a packaging material for semiconductor materials. This is presumably because industrial materials usually have an uneven shape, and therefore the packaging material is subjected to a force due to the uneven shape, and when the yield stress of the substrate is high, the packaging material is less likely to stretch and is less likely to break. The upper limit of the yield stress of the substrate is not particularly limited, but may be, for example, 500 MPa or 400 MPa. The yield stress is a tensile yield stress measured in accordance with JIS K7161-1:2014. Specifically, a test piece having a width of 15 mm and a length of 50 mm is prepared, and the test piece is pulled at a speed of 50 mm / min using a tensile tester to measure the yield stress. The substrate preferably has a yield stress equal to or greater than the lower limit in at least one tensile direction. For example, in the case of a uniaxially stretched substrate, the yield stress when the tensile direction is the stretching direction is preferably equal to or greater than the lower limit.

[0045] Examples of the substrate include: A base material containing high density polyethylene as a main component, A multilayer substrate comprising a first layer containing a medium density polyethylene as a main component, a second layer containing a high density polyethylene as a main component, a third layer containing a linear low density polyethylene as a main component, a fourth layer containing a medium density polyethylene as a main component, and a fifth layer containing a medium density polyethylene as a main component; A multilayer substrate comprising a barrier resin layer (first layer), an adhesive resin layer (second layer), a third layer containing linear low-density polyethylene as a main component, a layer containing linear low-density polyethylene and medium-density polyethylene, and a fifth layer containing medium-density polyethylene as a main component; Examples include:

[0046] Examples of the substrate include: A stretched substrate containing high density polyethylene as a main component, An unstretched substrate containing high density polyethylene as a main component; A stretched multilayer substrate comprising a first layer containing medium density polyethylene as a main component, a second layer containing high density polyethylene as a main component, a third layer containing linear low density polyethylene as a main component, a fourth layer containing medium density polyethylene as a main component, and a fifth layer containing medium density polyethylene as a main component; a stretched multilayer substrate comprising a barrier resin layer (first layer), an adhesive resin layer (second layer), a third layer containing linear low-density polyethylene as a main component, a layer containing linear low-density polyethylene and medium-density polyethylene, and a fifth layer containing medium-density polyethylene as a main component; Among these, a stretched substrate containing high density polyethylene as a main component is preferred from the viewpoint of high yield stress and high puncture strength of the substrate.

[0047] (Polyethylene layer) The polyethylene layer contains polyethylene as a main component. The polyethylene content in the polyethylene layer is preferably more than 50% by mass, 60% by mass or more, or 70% by mass or more, more preferably 80% by mass or more, even more preferably 85% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more.

[0048] (Barrier resin layer) The substrate may include a barrier resin layer containing a gas barrier resin as a main component. Such a substrate has excellent heat resistance, strength, rigidity, and gas barrier properties such as oxygen barrier property and water vapor barrier property.

[0049] Examples of gas barrier resins include polyamide, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyvinylidene chloride, polyester, polyether polyol, polyester polyol, polyurethane, polyacrylonitrile, and (meth)acrylic resin. Among these, polyamide is preferred from the viewpoint of the puncture strength of the substrate.

[0050] The polyamide may be, for example, an aliphatic polyamide or a semi-aromatic polyamide. The polyamide is preferably an aliphatic polyamide, more preferably a crystalline aliphatic polyamide. The polyamide is also preferably a semi-aromatic polyamide, more preferably an amorphous semi-aromatic polyamide. The polyamide may be a mixture of an aliphatic polyamide and a semi-aromatic polyamide.

[0051] Examples of the aliphatic polyamide include aliphatic homopolyamide and aliphatic copolymer polyamide. In the following examples, polyamide is also referred to as "PA."

[0052] Specific examples of aliphatic homopolyamides include polycaprolactam (PA6), polyenantholactam (PA7), polyundecane lactam (PA11), polylauryl lactam (PA12), polyhexamethylene adipamide (PA66), polytetramethylene dodecamide (PA412), polypentamethylene azelamide (PA59), polypentamethylene sebacamide (PA510), polypentamethylene dodecamide (PA512), polyhexamethylene azelamide (PA69), polyhexamethylene sebacamide (PA610), polyhexamethylene dodecamide (PA612), poly Nonamethylene adipamide (PA96), polynonamethylene azelamide (PA99), polynonamethylene sebacamide (PA910), polynonamethylene dodecamide (PA912), polydecamethylene adipamide (PA106), polydecamethylene azelamide (PA109), polydecamethylene decamamide (PA1010), polydecamethylene dodecamide (PA1012), polydodecamethylene adipamide (PA126), polydodecamethylene azelamide (PA129), polydodecamethylene sebacamide (PA1210) and polydodecamethylene dodecamide (PA1212).

[0053] Specific examples of aliphatic copolymer polyamides include caprolactam / hexamethylenediaminoadipic acid copolymer (PA6 / 66), caprolactam / hexamethylenediaminoazelaic acid copolymer (PA6 / 69), caprolactam / hexamethylenediaminosebacic acid copolymer (PA6 / 610), caprolactam / hexamethylenediaminoundecanoic acid copolymer (PA6 / 611), caprolactam / hexamethylenediaminododecanoic acid copolymer (PA6 / 612), caprolactam / amino undecanoic acid copolymer (PA6 / 11), caprolactam / lauryllactam copolymer (PA6 / 12), caprolactam / hexamethylenediaminoadipic acid / lauryllactam copolymer (PA6 / 66 / 12), caprolactam / hexamethylenediaminoadipic acid / hexamethylenediaminosebacic acid copolymer (PA6 / 66 / 610), caprolactam / hexamethylenediaminoadipic acid / hexamethylenediaminododecanedicarboxylic acid copolymer (PA6 / 66 / 612).

[0054] The relative viscosity of the aliphatic polyamide is preferably 1.5 or more, more preferably 2 or more, and even more preferably 2.5 or more. The relative viscosity of the aliphatic polyamide is preferably 5 or less, more preferably 4.5 or less. The relative viscosity of the aliphatic polyamide is measured at 25°C in accordance with JIS K6920-2:2009 by dissolving 1g of polyamide in 100mL of 96% concentrated sulfuric acid.

[0055] Examples of crystalline aliphatic polyamides include PA6, PA11, PA12, PA66, PA610, PA612, PA6 / 66, and PA6 / 66 / 12. The melting point (Tm) of the crystalline aliphatic polyamide is preferably 180° C. or higher. The Tm of the crystalline aliphatic polyamide is preferably 300° C. or lower, more preferably 250° C. or lower, and even more preferably 230° C. or lower.

[0056] The semi-aromatic polyamide is a polyamide having a constitutional unit derived from an aromatic diamine and a constitutional unit derived from an aliphatic dicarboxylic acid, or a polyamide having a constitutional unit derived from an aliphatic diamine and a constitutional unit derived from an aromatic dicarboxylic acid, for example, a polyamide composed of an aromatic diamine and an aliphatic dicarboxylic acid, or a polyamide composed of an aliphatic diamine and an aromatic dicarboxylic acid. The semi-aromatic polyamide, in one embodiment, is an amorphous semi-aromatic polyamide.

[0057] Examples of semi-aromatic polyamides include polyhexamethylene terephthalamide (PA6T), polyhexamethylene isophthalamide (PA6I), polynonamethylene terephthalamide (PA9T), polyhexamethylene adipamide / polyhexamethylene terephthalamide copolymer (PA66 / 6T), polyhexamethylene adipamide / polyhexamethylene isophthalamide copolymer (PA66 / 6I), polyhexamethylene terephthalamide / polycaproamide copolymer (PA6T / 6), polyhexamethylene isophthalamide / polycaproamide copolymer (PA6I / 6), polyhexamethylene terephthalamide / poly dodecamide copolymer (PA6T / 12), polyhexamethylene isophthalamide / polyhexamethylene terephthalamide copolymer (PA6I / 6T), polyhexamethylene terephthalamide / poly(2-methylpentamethylene terephthalamide) copolymer (PA6T / M5T), polyhexamethylene adipamide / polyhexamethylene terephthalamide / polyhexamethylene isophthalamide copolymer (PA66 / 6T / 6I), polyhexamethylene adipamide / polycaproamide / polyhexamethylene isophthalamide copolymer (PA66 / 6 / 6I) and polymetaxylylene adipamide (PAMXD6).

[0058] The melt volume rate (MVR) of the semi-aromatic polyamide is preferably 5 cm 3 / 10 minutes or more, preferably 10cm 3 The MVR of the semi-aromatic polyamide is preferably 200 cm 3 / 10 minutes or less, preferably 100cm 3 / 10 minutes or less. MVR is measured at a temperature of 275°C and a load of 5.00 kg in accordance with JIS K7210-1:2014.

[0059] The content of the gas barrier resin in the barrier resin layer is more than 50% by mass, preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more.

[0060] The barrier resin layer may contain the above-mentioned additives.

[0061] The thickness of the barrier resin layer is preferably 0.5 μm or more, more preferably 1 μm or more, and even more preferably 1.5 μm or more, from the viewpoint of the above-mentioned physical properties such as heat resistance and gas barrier property, etc. The thickness of the barrier resin layer is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 6 μm or less, from the viewpoint of recyclability of the substrate.

[0062] (adhesive resin layer) The substrate may further include an adhesive resin layer between the polyethylene layer and the barrier resin layer. Such a substrate has, for example, excellent adhesion between the polyethylene layer and the barrier resin layer.

[0063] The adhesive resin layer contains a resin material. Examples of the resin material include polyolefin, modified polyolefin, vinyl resin, silicone resin, epoxy resin, and phenol resin. Among these, from the viewpoint of recyclability and adhesion, polyolefin and modified polyolefin are preferred, modified polyolefin such as acid modified polyolefin are more preferred, and modified polyethylene such as acid modified polyethylene are even more preferred.

[0064] The modified polyolefin may be, for example, a polyolefin modified with an unsaturated carboxylic acid such as maleic acid or fumaric acid, or an acid anhydride, ester, or metal salt thereof, particularly a graft modified polyolefin. Specifically, the modified polyolefin is preferably an unsaturated carboxylic acid modified polyethylene, more preferably a maleic anhydride modified polyethylene.

[0065] The melt flow rate (MFR) of the modified polyolefin is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and even more preferably 0.5 g / 10 min or more, from the viewpoint of film-forming and processability. The MFR of the modified polyolefin is preferably 30 g / 10 min or less, more preferably 20 g / 10 min or less, even more preferably 10 g / 10 min or less, and particularly preferably 5 g / 10 min or less, from the viewpoint of film-forming and processability. The MFR of the modified polyolefin is measured by the A method under a load of 2.16 kg in accordance with JIS K7210-1:2014. The measurement temperature of the MFR is set according to the melting point of the modified polyolefin, and is 190° C. in the case of modified polyethylene.

[0066] The adhesive resin layer may contain the above-mentioned additives.

[0067] From the viewpoint of the adhesion, the thickness of the adhesive resin layer is preferably 0.5 μm or more, more preferably 1 μm or more, and from the viewpoint of the recyclability of the substrate, the thickness of the adhesive resin layer is preferably 15 μm or less, more preferably 10 μm or less.

[0068] <Adhesive layer> The laminate of the present disclosure includes an adhesive layer between the substrate and the sealant layer. Examples of the adhesive layer include an adhesive layer made of an adhesive and an extruded resin layer containing polyethylene as a main component.

[0069] In one embodiment, the laminate of the present disclosure includes an adhesive layer formed of an adhesive between the substrate and the sealant layer. Such a laminate has, for example, excellent interlayer adhesion strength.

[0070] The adhesive may be any of a one-component curing adhesive, a two-component curing adhesive, and a non-curing adhesive. The adhesive may be a solvent-based adhesive or a solventless adhesive. Examples of the solvent-based adhesive include rubber-based adhesives, vinyl-based adhesives, olefin-based adhesives, silicone-based adhesives, epoxy-based adhesives, phenol-based adhesives, and urethane-based adhesives. Examples of the solventless adhesive include polyether-based adhesives, polyester-based adhesives, silicone-based adhesives, epoxy-based adhesives, and urethane-based adhesives. Among these, urethane-based adhesives are preferred, and two-component curing urethane-based adhesives are more preferred.

[0071] Examples of methods for coating the adhesive layer include direct gravure roll coating, gravure roll coating, kiss coating, reverse roll coating, Fontaine method, and transfer roll coating.

[0072] The thickness of the adhesive layer is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.5 μm or more. The thickness of the adhesive layer is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 6 μm or less.

[0073] The laminate of the present disclosure can be produced by laminating the substrate and the sealant film as the sealant layer by a lamination method using the above adhesive, and may be produced by laminating, for example, by a dry lamination method using a solvent-based adhesive, or by a non-solvent lamination method using a solventless adhesive. When the laminate is used for a packaging bag, the non-solvent lamination method is preferred from the viewpoint of reducing contamination of the contents.

[0074] In one embodiment, the laminate of the present disclosure includes an extruded resin layer containing polyethylene as a main component between the substrate and the sealant layer. Such a laminate can have a higher polyethylene content than a laminate including an adhesive layer made of a conventional non-polyethylene adhesive (e.g., a two-component curing polyurethane adhesive). Such a laminate has excellent recyclability.

[0075] The extruded resin layer contains polyethylene as a main component. The polyethylene in the extruded resin layer and the polyethylene in the substrate and sealant layer may be the same or different.

[0076] The polyethylene contained in the extruded resin layer is preferably high-density polyethylene, medium-density polyethylene, low-density polyethylene, or linear low-density polyethylene, and from the viewpoint of adhesiveness, low-density polyethylene or linear low-density polyethylene is more preferable, and low-density polyethylene is even more preferable.

[0077] From the viewpoints of film-forming ability and processability, the MFR of the polyethylene in the extruded resin layer is preferably 0.1 g / 10 min or more, more preferably 1 g / 10 min or more, even more preferably 3 g / 10 min or more, and is preferably 30 g / 10 min or less, more preferably 25 g / 10 min or less, even more preferably 20 g / 10 min or less.

[0078] From the viewpoint of a balance between heat resistance and adhesiveness, the melting point (Tm) of the polyethylene in the extruded resin layer is preferably 100°C or higher, and preferably 140°C or lower, more preferably 130°C or lower, and even more preferably 120°C or lower.

[0079] The content of polyethylene in the extruded resin layer is preferably 80% by mass or more, more preferably 85% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass. A laminate including such an extruded resin layer has, for example, excellent adhesion and recyclability.

[0080] The thickness of the extruded resin layer is preferably 5 μm or more, more preferably 10 μm or more, and is preferably 40 μm or less, more preferably 30 μm or less. A laminate including such an extruded resin layer has, for example, excellent interlayer adhesion and recyclability.

[0081] The extruded resin layer can be formed, for example, by melting polyethylene or a polyethylene composition and extruding it onto a substrate at a melting temperature of preferably 280° C. or higher, more preferably 290° C. or higher, and preferably 340° C. or lower, more preferably 335° C. or lower.

[0082] As a method for bonding the substrate and the sealant film as the sealant layer, for example, a melt extrusion lamination method using a molten resin containing polyethylene as a main component, particularly a sand lamination method, can be used. This can increase the polyethylene content of the laminate, for example. In addition, compared to laminating them by dry lamination, the time required for the drying process and the aging process can be reduced, and therefore the production efficiency of the laminate can be improved.

[0083] <Sealant layer> The laminate of the present disclosure includes a sealant layer. When a packaging bag is produced using the laminate of the present disclosure, for example, the substrate is a layer facing the outside of the packaging bag, and the sealant layer is a layer facing the storage space of the packaging bag (the innermost layer of the packaging bag).

[0084] The sealant layer contains polyethylene as a main component. The polyethylene contained in the sealant layer is preferably high-density polyethylene, medium-density polyethylene, low-density polyethylene, or linear low-density polyethylene, and from the viewpoint of heat sealability, low-density polyethylene or linear low-density polyethylene is more preferable, and linear low-density polyethylene is even more preferable.

[0085] From the viewpoints of film-forming property and processability, the MFR of the polyethylene contained in the sealant layer is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and even more preferably 0.5 g / 10 min or more. From the viewpoints of film-forming property and processability, the MFR of the polyethylene is preferably 30 g / 10 min or less, more preferably 20 g / 10 min or less, even more preferably 10 g / 10 min or less, and particularly preferably 5 g / 10 min or less.

[0086] From the viewpoint of heat sealability, the melting point (Tm) of the polyethylene contained in the sealant layer is preferably 80°C or higher, more preferably 90°C or higher, and preferably 140°C or lower, more preferably 130°C or lower, and even more preferably 120°C or lower.

[0087] The content of polyethylene in the sealant layer is more than 50% by mass, preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more. A laminate having such a sealant layer has, for example, excellent recyclability.

[0088] The sealant layer may contain the above-mentioned additives.

[0089] The sealant layer may have a single-layer structure or a multi-layer structure. The thickness of the sealant layer is preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, even more preferably 40 μm or more, and particularly preferably 50 μm or more. The thickness of the sealant layer is preferably 140 μm or less, more preferably 135 μm or less, even more preferably 130 μm or less, even more preferably 125 μm or less, and particularly preferably 120 μm or less. From the viewpoint of strength and processing suitability, it is preferable that the thickness of the sealant layer is appropriately changed depending on the mass of the industrial material contained in the packaging bag.

[0090] The sealant layer is preferably an unstretched layer from the viewpoint of heat sealability. Therefore, the sealant film corresponding to the sealant layer is preferably an unstretched film from the viewpoint of heat sealability. The concept of "unstretched" includes not only a layer or film that is not stretched at all, but also a layer or film that is slightly stretched due to the tension applied during film formation. Details of the stretching process are as described above in the explanation of the substrate. The sealant film can be produced by a conventionally known method. The sealant film can be produced, for example, by a T-die method or an inflation method.

[0091] When the industrial material is a semiconductor material, it is preferable that no metal elements are present on the surface of the sealant layer that contacts the semiconductor material. An example of such a sealant layer is an additive-free sealant layer that causes little elution of metal elements. It is also preferable that dust and dirt are less likely to adhere to the surface of the sealant layer during transportation. An example of such a sealant layer is an antistatic sealant layer. It is also possible to select a sealant that suppresses elution of the antistatic sealant layer by conducting a metal elution test.

[0092] The additive-free sealant layer is a polyethylene sealant that does not contain any additives, including antioxidants, light stabilizers, metal deactivators, slip agents, antistatic agents, antiblocking agents, antifogging agents, etc. The thickness of the additive-free sealant layer is preferably 60 μm or more, more preferably 80 μm or more, and even more preferably 100 μm or more.

[0093] The antistatic performance of the antistatic sealant layer can be evaluated by the surface resistance value of the surface (sealing surface) of the sealant layer. The surface resistance value of the sealant layer is preferably 1.0×10 10 Ω or more, preferably 1.0×10 9 Ω or more, more preferably 1.0×10 8 Ω or more, and preferably 1.0×10 13 Ω or less, more preferably 1.0×10 12Ω or less, more preferably 1.0×10 11 When the surface resistance of the sealant layer is in the above range, it is preferable since it prevents adhesion of dust and dirt and protects the semiconductor products and electronic parts contained therein.

[0094] <Heat-resistant coating layer> The laminate of the present disclosure includes a heat-resistant coating layer on one side of a substrate. When a packaging bag is produced using the laminate of the present disclosure, for example, the heat-resistant coating layer is a layer facing the outside of the packaging bag (the outermost layer of the packaging bag), and the sealant layer is a layer facing the storage space of the packaging bag (the innermost layer of the packaging bag).

[0095] The heat-resistant coating layer is a layer made of a heat-resistant coating agent. By providing a heat-resistant coating layer on one side of the substrate, the laminate of the present disclosure can be imparted with extremely high heat resistance when heat-sealing the laminate. In addition, the laminate of the present disclosure is provided with a heat-resistant coating layer, and therefore has excellent abrasion resistance and pinhole resistance.

[0096] The thickness of the heat-resistant coating layer is not particularly limited, and can be appropriately selected according to the heat resistance temperature required for the laminate of the present disclosure. The thickness of the heat-resistant coating layer is preferably 0.3 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. When the thickness is 0.3 μm or more, sufficient heat resistance can be imparted to the laminate of the present disclosure. In addition, the thickness of the heat-resistant coating layer is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. When the thickness is 20 μm or less, the polyethylene content in the laminate of the present disclosure is easily set to 80 mass% or more, and the laminate has excellent recyclability.

[0097] The heat-resistant coating agent used in the heat-resistant coating layer is not particularly limited, and can be appropriately selected according to the film thickness and heat resistance required for the laminate of the present disclosure. Examples of the heat-resistant coating agent include cellulose acetate-based coating agents, urethane-based coating agents, polyvinyl chloride-based coating agents, and polyvinyl chloride-vinyl acetate copolymer-based coating agents.

[0098] Examples of cellulose acetate-based coating agents include cellulose acetate and cellulose acetate butyrate, which are semi-synthetic polymers obtained by esterifying cellulose, a natural polymer.

[0099] Examples of urethane-based coating agents include resins that are cured by forming a urethane bond between a polyol and a crosslinking agent such as a polyisocyanate compound. Examples of polyols that can be used include acrylic polyols and polyester polyols.

[0100] An example of the polyvinyl chloride coating agent is a polyvinyl chloride resin. As the polyvinyl chloride-vinyl acetate copolymer coating agent, it is preferable to use a vinyl chloride-vinyl acetate copolymer resin. The vinyl chloride-vinyl acetate copolymer resin is not particularly limited as long as it is a copolymer of vinyl chloride and vinyl acetate.

[0101] As a crosslinking agent for any of the base compounds, the isocyanate compounds are 1,4-tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate, 1,12-dodecamethylene diisocyanate, cyclohexane-1,3- or 1,4-diisocyanate, 1-isocyanato-3-isocyanatomethyl-3,5,5-trimethylcyclohexane (also known as isophorone diisocyanate; IPDI), dicyclohexylmethane-4,4'-diisocyanate (also known as hydrogenated MDI), 2- or 4-isocyanatocyclohexyl-2'-isocyanatocyclohexylmethane, 1,3- or 1,4-bis-(iso bis-(4-isocyanatomethyl)cyclohexane, bis-(4-isocyanato-3-methylcyclohexyl)methane, 1,3- or 1,4-α,α,α'α'-tetramethylxylylene diisocyanate, 2,4- or 2,6-diisocyanatotoluene, 2,2'-, 2,4'- or 4,4'-diisocyanatodiphenylmethane (MDI), 1,5-naphthalene diisocyanate, p- or m-phenylene diisocyanate, xylylene diisocyanate or diphenyl-4,4'-diisocyanate, tolylene diisocyanate (TDI), xylylene diisocyanate (XDI), and the like.

[0102] The heat-resistant coating layer can be formed by applying the heat-resistant coating agent onto one surface of the substrate, and then volatilizing the solvent component contained in the heat-resistant coating agent.

[0103] The substrate is preferably a stretched substrate mainly composed of polyethylene. The stretched substrate has a superior surface smoothness compared to an unstretched substrate, and therefore the heat-resistant coating agent can be uniformly applied to the surface of the substrate.

[0104] In addition, the application of the heat-resistant coating agent to the substrate is preferably performed before laminating the stretched substrate as the substrate with the sealant layer via the extruded resin layer as the adhesive layer. The heat-resistant coating agent contains a diluent, which contains a small amount of metal ions. Therefore, the heat-resistant coating agent is applied to the substrate before laminating with the extruded resin layer, and then the diluent is volatilized by keeping the substrate at about 40°C, so that the heat-resistant coating agent can be completely cured. Then, the substrate provided with the heat-resistant coating layer and the sealant layer are laminated with the extruded resin layer, so that the components contained in the heat-resistant coating agent can be prevented from being transferred to the surface of the sealant layer. In addition, the lamination of the substrate and the sealant layer with the extruded resin layer is performed at about 300°C, so that even if the solvent components of the heat-resistant coating agent remain in the heat-resistant coating layer provided on the substrate, they can be reliably volatilized and removed.

[0105] The amount of the heat-resistant coating agent applied to the substrate can be appropriately selected depending on the type of the heat-resistant coating agent and the thickness of the heat-resistant coating layer to be formed. The amount of application is preferably 0.5 g / m 2 More preferably, 1.0 g / m 2 More preferably, it is 3.0 g / m or more. 2 Less than 2.0 g / m, more preferably 2.0 g / m 2 For example, 0.5 g / m 2 More than 3.0g / m 2 The following is the result.

[0106] The heat-resistant coating layer may be a single layer or may have a laminated structure of two or more layers. When the heat-resistant coating layer is a single layer, one type of heat-resistant coating agent may be used, or two or more types of heat-resistant coating agents may be used in combination (mixed). When the heat-resistant coating layer has a laminated structure of two or more layers, the type, content and coating amount of the heat-resistant coating agent may be appropriately selected for each layer, and these may be combined to form any layer structure.

[0107] <Anchor coat layer> The laminate of the present disclosure may include an anchor coat layer on the other side of the substrate, i.e., on the side opposite to the heat-resistant coating layer. The anchor coat layer is located between the substrate and the adhesive layer. In one embodiment, the laminate of the present disclosure may include a heat-resistant coating layer, a substrate, an anchor coat layer, an adhesive layer, and a sealant layer in this order.

[0108] The anchor coat layer is a layer made of an anchor coat agent. By providing the anchor coat layer between the substrate and the adhesive layer, the adhesion between the substrate and the adhesive layer can be improved.

[0109] The thickness of the anchor coat layer is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. When the thickness is 0.1 μm or more, sufficient adhesion can be imparted to the laminate of the present disclosure. In addition, the thickness of the anchor coat layer is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less. When the thickness is 10 μm or less, the polyethylene content in the laminate of the present disclosure is easily set to 80 mass% or more, and the laminate has excellent recyclability.

[0110] The anchor coating agent used in the anchor coating layer is not particularly limited, and can be appropriately selected according to the film thickness and adhesion required for the laminate of the present disclosure. The anchor coating agent can be any resin with a heat resistance temperature of 135°C or higher, such as an anchor coating agent made of vinyl modified resin, epoxy resin, urethane resin, polyester resin, polyethyleneimine, etc., and can be preferably used as a cured product of a polyacrylic or polymethacrylic resin (polyol) having two or more hydroxyl groups in the structure and an isocyanate compound as a curing agent. In addition, a silane coupling agent may be used in combination with this as an additive, and nitrocellulose may be used in combination to increase heat resistance.

[0111] The anchor coat layer can be formed by applying the anchor coat agent to one side of the substrate and then volatilizing the solvent component contained in the anchor coat. The amount of the anchor coat agent applied to the substrate can be appropriately selected depending on the type of the anchor coat agent and the thickness of the anchor coat layer to be formed.

[0112] <Print layer> The laminate of the present disclosure may further include a printed layer provided on one or both surfaces of the substrate. In one embodiment, the laminate of the present disclosure may include a substrate, a printed layer, an adhesive layer, and a sealant layer in this order.

[0113] The print layer includes an image. Examples of the image include characters, figures, patterns, symbols, and combinations thereof. The image may include text information such as the product name, the name of the item in the packaging bag, the manufacturer, and the names of ingredients. The image may be a single, solid color (so-called solid image).

[0114] The printed layer, in one embodiment, contains a colorant. Examples of colorants include pigments such as inorganic pigments and organic pigments, as well as dyes such as acid dyes, direct dyes, disperse dyes, oil-soluble dyes, metal-containing oil-soluble dyes, and sublimation dyes. Examples of colorants also include fluorescent materials such as ultraviolet emitting materials that emit fluorescence by absorbing ultraviolet light, and infrared emitting materials that emit fluorescence by absorbing infrared light.

[0115] The content of the colorant in the printed layer is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more. The content of the colorant in the printed layer is preferably 90% by mass or less, more preferably 70% by mass or less, and even more preferably 50% by mass or less.

[0116] In one embodiment, the print layer contains a resin material in addition to a colorant. Examples of the resin material include thermoplastic resins, cured products of thermosetting resins, and cured products of energy ray curable compounds. Examples of the thermoplastic resins include polyolefins, chlorinated polyolefins, polystyrenes, (meth)acrylic resins, vinyl resins, acetal resins, polyesters, polyurethanes, polycarbonates, polyamides, polyimides, cellulose resins, petroleum resins, and fluororesins. Examples of the thermosetting resins include phenolic resins, melamine resins, urea resins, epoxy resins, unsaturated polyesters, thermosetting polyurethanes, silicone resins, and (meth)acrylic thermosetting resins. Examples of the energy ray curable compounds include polyfunctional (meth)acrylate compounds.

[0117] The content of the resin material in the printed layer is preferably 10% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more. The content of the resin material in the printed layer is preferably 99% by mass or less, more preferably 97% by mass or less, and even more preferably 95% by mass or less.

[0118] The printing layer may contain the above-mentioned additives.

[0119] The printing layer can be formed, for example, using an ink composition containing the above-mentioned components and, if necessary, a solvent. Methods for forming the printing layer include, for example, gravure printing, offset printing, flexographic printing, screen printing, letterpress printing, and transfer printing. From the viewpoint of reducing the environmental load, the printing layer may be formed by flexographic printing. From the viewpoint of reducing the environmental load, the printing layer may be formed using an ink derived from biomass.

[0120] The thickness of the printed layer is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. The thickness of the printed layer is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less.

[0121] (Laminate) The laminate of the present disclosure has a puncture strength of preferably 7N or more, more preferably 8N or more, and even more preferably 9N or more. The present inventors have found that a laminate having a puncture strength equal to or greater than the above lower limit is suitable as a packaging material for industrial materials, particularly a packaging material for semiconductor materials. This is presumably because industrial materials usually have an uneven shape, and therefore the packaging material is subjected to a force due to the uneven shape, and when the puncture strength of the laminate is high, the packaging material is less likely to stretch and tear. The upper limit of the puncture strength of the laminate is not particularly limited, but may be, for example, 10N or 15N.

[0122] The puncture strength is measured in accordance with JIS Z1707:2019. Specifically, the laminate (packaging material) is cut to prepare a test piece having a width of 5 cm and a length of 5 cm. In a measurement environment of 23°C temperature and 50% RH humidity, a Tensilon universal material testing machine RCT-1350A (manufactured by AND Co., Ltd.) is used as a measuring instrument, and a semicircular needle having a diameter of 1.0 mm and a tip shape radius of 0.5 mm is pierced into the test piece at a test speed of 50 mm / min, and the maximum strength (N) until the needle penetrates the test piece is measured. In the case of a polyethylene-based laminate, the needle is pierced into the substrate surface to measure the puncture strength (N). Measurements are performed on three test pieces for each, and the arithmetic average value of the three values ​​obtained is taken as the puncture strength.

[0123] The laminate of the present disclosure has a heat resistance temperature of preferably 160° C. or higher, more preferably 170° C. or higher, and even more preferably 180° C. or higher. A polyethylene-based laminate having a heat resistance temperature of the above-mentioned lower limit or higher has high heat resistance of the substrate in contact with the heat seal bar, so that even when heat-sealed at high temperatures, the substrate can be heat-sealed without being taken by the heat seal bar. The method for evaluating the heat resistance of the laminate of the present disclosure will be described in the examples below.

[0124] [Packaging bags and packaging bodies] The packaging bag of the present disclosure comprises the laminate of the present disclosure. The packaging bag of the present disclosure is, for example, one or more laminates of the present disclosure; a seal portion in which the sealant layers of the laminate are joined together; A storage section for storing industrial materials; Equipped with. The seal portion includes an inner edge that defines the receiving portion.

[0125] The packaging of the present disclosure comprises: The packaging bag of the present disclosure; Industrial materials contained in the packaging bag; Equipped with.

[0126] In one embodiment, the packaging bag of the present disclosure includes a top sheet constituting the top surface and a back sheet constituting the back surface. The top sheet may be made of one laminate of the present disclosure, and the back sheet may be made of another laminate of the present disclosure. The top sheet and the back sheet may be integrated together, or may be made of one laminate of the present disclosure. The top sheet and the back sheet may be made of one tubular laminate of the present disclosure.

[0127] Examples of methods for forming the sealed portion include heat sealing, which involves melting the sealant layer of the laminate by heating or the like to fuse the sealant layers together, and specifically include bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, and ultrasonic sealing. For example, after industrial materials are placed in a packaging bag, the opening of the packaging bag can be heat sealed to seal the packaging bag.

[0128] Examples of packaging bags include packaging bags of various shapes such as a standing pouch type, a side seal type, a two-sided seal type, a three-sided seal type, a four-sided seal type, an envelope seal type, a grooving seal type (pillow seal type), a pleated seal type, a flat bottom seal type, a square bottom seal type, and a gusset type. The planar shape of the packaging bag may be, for example, rectangular or a shape other than rectangular, such as a circle.

[0129] The packaging bag may have an easy-to-open portion. Examples of the easy-to-open portion include a notch portion that serves as a starting point for tearing the packaging bag, and a half-cut line formed by laser processing or a cutter as a path for tearing the packaging bag.

[0130] In one embodiment, a packaging bag can be produced by folding the laminate of the present disclosure in half and stacking them so that the base material is on the outside and the sealant layer is on the inside, and then heat-sealing the ends, etc. In another embodiment, a packaging bag can be produced by stacking multiple laminates of the present disclosure so that the sealant layers face each other, and then heat-sealing the ends, etc. The entire packaging bag may be made of the above-mentioned laminate, or only a part of the packaging bag may be made of the above-mentioned laminate.

[0131] An example of producing a packaging bag using the laminate of the present disclosure will be described. Two laminates are prepared. The two laminates are stacked together with the sealant layers facing each other. Next, heat seals are formed on the outer periphery of the laminate, on the left, right, and bottom. In this way, a packaging bag with an opening on one side is obtained.

[0132] Instead of using two sheets of the laminate of the present disclosure, one sheet of the laminate of the present disclosure may be prepared, folded and stacked so that the sealant layers of the laminate face each other, and then heat-sealed portions may be formed on both the left and right outer peripheral edges to produce a packaging bag. In this way, a packaging bag having an opening on one side is obtained. In this case, a heat-sealed portion may also be formed on the folded-back lower portion.

[0133] The industrial material is placed into the opening of the unheat-sealed portion of the packaging bag produced above. The opening of the packaging bag is then heat-sealed to form a heat-sealed portion, thereby obtaining a package in which the industrial material is housed in the packaging bag.

[0134] Examples of the industrial materials include semiconductor materials such as silicon materials (e.g., polysilicon materials) and silicon wafers, metal materials, electronic components such as integrated circuits (ICs), capacitors, and semiconductor elements, semiconductor-related components such as valves for semiconductor devices and filters for semiconductor manufacturing, precision machinery, magnetic disks, O-rings, and bellows. Among these, semiconductor materials are preferred, silicon materials are more preferred, and polysilicon materials are even more preferred.

[0135] The present disclosure relates to, for example, the following [1] to

[11] . [1] A packaging material comprising at least a heat-resistant coating layer, a substrate, an adhesive layer, and a sealant layer in this order, The substrate contains polyethylene as a main component, The sealant layer contains polyethylene as a main component, The total thickness is 150 μm or less. packaging materials. [2] The packaging material according to [1] above, wherein the heat-resistant coating layer is a layer made of a cellulose acetate-based coating agent, a urethane-based coating agent, a polyvinyl chloride-based coating agent, or a polyvinyl chloride-vinyl acetate copolymer-based coating agent. [3] The packaging material according to [1] or [2] above, wherein the substrate is a stretched substrate containing polyethylene as a main component. [4] The packaging material according to any one of [1] to [3] above, wherein the substrate is a stretched substrate containing high-density polyethylene as a main component. [5] The packaging material according to any one of [1] to [4] above, wherein the sealant layer is an unstretched layer. [6] The packaging material according to any one of [1] to [5] above, wherein the adhesive layer includes an extruded resin layer containing polyethylene as a main component. [7] The packaging material according to any one of [1] to [6] above, wherein the content of polyethylene in the entire packaging material is 80 mass % or more. [8] The packaging material according to any one of [1] to [7] above, which is for industrial materials. [9] The packaging material according to [8], wherein the industrial material is a semiconductor material.

[10] A packaging bag comprising the packaging material according to any one of [1] to [9].

[11] The packaging bag according to

[10] above, Industrial materials contained in the packaging bag; A packaging body comprising:

[12] The packaging body described in

[11] , wherein the industrial material is a semiconductor material. EXAMPLES

[0136] The laminate of the present disclosure will be described in more detail with reference to examples, but the laminate of the present disclosure is not limited to the examples. In the following description, "parts by mass" will be simply referred to as "parts".

[0137] [Preparation of substrate] The components used in preparing the substrate are shown below. High density polyethylene The Dow Chemical Company, ELITE 5960G, Density: 0.962g / cm 3 Melting point: 134℃, MFR: 0.85g / 10min High density polyethylene SCG company, H619F, Density: 0.965g / cm 3 , MFR:0.70g / 10min Medium density polyethylene ExxonMobil, Enable 4002MC, Density: 0.940g / cm 3 Melting point: 128℃, MFR: 0.25g / 10min Low density polyethylene PTT, LD2420F, Density: 0.922g / cm 3 Melting point: 112℃, MFR: 0.75g / 10min Linear low density polyethylene ExxonMobil, Exceed XP8656ML, Density: 0.916g / cm 3 Melting point: 121℃, MFR: 0.5g / 10min Linear low density polyethylene ExxonMobil, Exceed 1327MA, Density: 0.927g / cm 3 Melting point: 123℃, MFR: 1.3g / 10min ·Masterbatch containing slip agent (MB) Ampacet, SLIP61 10061-K, Density: 0.910g / cm 3 , MFR:10g / 10min Nylon 6 / 66C BASF, Ultramid C33, Density: 1.12g / cm 3 , Melting point: 196°C, Viscosity number: 195, Relative viscosity: 3.3 Amorphous semi-aromatic polyamide EMS, Grivory G21, Density: 1.18g / cm 3 , MVR:20cm 3 / 10 minutes ·Adhesive resin Mitsui Chemicals, ADMER AT1955E, Maleic anhydride grafted polyethylene, Density: 0.890g / cm 3 , MFR: 2.6g / 10min

[0138] [Stretched film (substrate 1)] Blended polyethylene A was obtained by mixing 70 parts of a medium density polyethylene (Enable 4002MC) and 30 parts of a high density polyethylene (ELITE 5960G). Blended polyethylene B was obtained by mixing 70 parts of medium density polyethylene (Enable 4002MC) and 30 parts of low density polyethylene (LD2420F). Blended polyethylene C was obtained by mixing 98 parts of linear low density polyethylene (Exceed XP8656ML) and 2 parts of MB containing slip agent (SLIP61 10061-K).

[0139] Blend polyethylene A, high density polyethylene (H619F), blend polyethylene C and blend ethylene B were extruded by inflation molding to form a tubular film with a layer thickness ratio of blend polyethylene A-1 layer (15 μm) / high density polyethylene layer (20 μm) / blend polyethylene C layer (55 μm) / blend polyethylene B layer (20 μm) / blend polyethylene A-2 layer (15 μm). A polyethylene film with a total thickness of 125 μm was obtained, and the tubular film was folded at the nip to form two layers. The numbers in parentheses indicate the layer thickness. The polyethylene film produced above was stretched in the longitudinal direction (MD) at a stretching ratio of 5 times, and the blend polyethylene A-2 layer was subjected to corona discharge treatment, and then the end was slit and divided into two pieces to obtain a stretched film with a thickness of 25 μm (hereinafter also referred to as "substrate 1"). The other side was also subjected to corona discharge treatment. Substrate 1 comprises a 3 μm thick blended polyethylene A-1 layer, a 4 μm thick high density polyethylene layer, a 11 μm thick blended polyethylene C layer, a 4 μm thick blended polyethylene B layer, and a 3 μm thick blended polyethylene A-2 layer.

[0140] [Stretched film (substrate 2)] A blended nylon was obtained by mixing 80 parts of nylon 6 / 66C (Ultramid C33) and 20 parts of an amorphous semi-aromatic polyamide (Grivory G21). Blended polyethylene D was obtained by mixing 50 parts of a linear low density polyethylene (Exceed XP8656ML) and 50 parts of a medium density polyethylene (Enable 4002MC). Blended polyethylene E was obtained by mixing 70 parts of a medium density polyethylene (Enable 4002MC) and 30 parts of a linear low density polyethylene (Exceed 1327MA).

[0141] Blended nylon, adhesive resin (ADMER AT1955E), linear low density polyethylene (Exceed XP8656ML), blended polyethylene D and blended polyethylene E were co-extruded by inflation molding to form a tubular film with a layer thickness ratio of blended nylon layer (10 μm) / adhesive resin layer (10 μm) / linear low density polyethylene layer (40 μm) / blended polyethylene D layer (20 μm) / blended polyethylene E layer (20 μm). A film with a total thickness of 100 μm was obtained, and the tubular film was folded at the nip to form two layers. This film was stretched in the longitudinal direction (MD) at a stretch ratio of 4 times, and the blended polyethylene E layer was subjected to corona discharge treatment, and then the end was slit and divided into two pieces to obtain a stretched film with a thickness of 25 μm (hereinafter also referred to as "substrate 2"). The other side was also subjected to corona discharge treatment. The substrate 2 comprises a 2.5 μm thick blended nylon layer, a 2.5 μm thick adhesive resin layer, and three 20 μm thick polyethylene layers.

[0142] [Base material] The stretched polyethylene film (hereinafter referred to as PEF) used was BOPE-TEN (thickness: 25 μm) manufactured by WEIFE.

[0143] [Sealant film] High density polyethylene film (hereinafter PEF1) (Dow Chemical, ELITE5960G, density: 0.962g / cm 3 A 200 μm-thick film was produced by forming a copolymer of 1,2-difluorophenyl ether (polymer having a melting point of 134° C. and a melting point of 0.85 g / 10 min) into a film by an inflation molding method.

[0144] As other sealant films, polyethylene films of the following grades were used. LA-7: Tamapoly Co., Ltd., 70 μm thick antistatic PEF (suppresses elution) SK615P: Tamapoly Co., Ltd., 100μm thick additive-free PEF L-140R-1: Aicello, 100μm thick antistatic PEF (soluble) L-535: Aicello, 100μm thick additive-free PEF TUX-VCS: Mitsui Chemicals Tocello Co., Ltd., low-temperature PEF with a thickness of 30 μm

[0145] [Heat-resistant coating agent] The following heat-resistant coating agent was used. ·Urethane-based heat-resistant coating agent A heat-resistant coating agent (hereinafter also referred to as "heat-resistant coating agent 1") was prepared by adding 100 parts of LG6720 Weak Matte Varnish B (manufactured by Tokyo Ink Co., Ltd.), 10 parts of LG Hardener D (manufactured by Tokyo Ink Co., Ltd.), and 30 parts of SL9170 Solvent (manufactured by Tokyo Ink Co., Ltd.) to a container equipped with a stirrer. Cellulose acetate-based heat-resistant coating agent In the same manner as in the case of heat-resistant coating 1, 100 parts of cellulose acetate butyrate solution (solid content 20%), 2.0 parts of xylylene diisocyanate (XDI), and 50 parts of ethyl acetate were added to a container equipped with a stirrer to prepare a heat-resistant coating agent (hereinafter also referred to as "heat-resistant coating agent 2").

[0146] [Example 1] The substrate was a 25 μm-thick biaxially oriented PEF (BOPE-TEN) with a corona treatment surface. Heat-resistant coating agent 2 was applied at a coating weight of 0.3 g / cm. 3 The corona-treated surface opposite the heat-resistant coating layer was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3 A polyethylene laminate of Example 1 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106° C., company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 70 μm-thick PEF (LA-7) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0147] [Example 2] The substrate was a 25 μm-thick biaxially oriented PEF (BOPE-TEN) with a corona treatment surface. Heat-resistant coating agent 2 was applied at a coating rate of 0.5 g / cm. 3 The corona-treated surface opposite the heat-resistant coating layer was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3 A polyethylene laminate of Example 2 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106° C., company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 70 μm-thick PEF (LA-7) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0148] [Example 3] The substrate was a 25 μm-thick biaxially oriented PEF (BOPE-TEN) with a corona treatment surface. Heat-resistant coating agent 2 was applied at a coating rate of 2.0 g / cm. 3 The corona-treated surface opposite the heat-resistant coating layer was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3 A polyethylene laminate of Example 3 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106° C., company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 70 μm-thick PEF (LA-7) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0149] [Example 4] The substrate was a 25 μm-thick biaxially oriented PEF (BOPE-TEN) with a corona treatment surface. Heat-resistant coating agent 2 was applied at a coating weight of 3.0 g / cm. 3The corona-treated surface opposite the heat-resistant coating layer was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3 A polyethylene laminate of Example 4 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106° C., company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 70 μm-thick PEF (LA-7) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0150] [Example 5] The substrate was a 25 μm-thick biaxially oriented PEF (BOPE-TEN) with a corona treatment surface. Heat-resistant coating agent 1 was applied at a coating weight of 0.3 g / cm. 3 The corona-treated surface opposite the heat-resistant coating layer was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3 A polyethylene laminate of Example 5 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106° C., company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 70 μm-thick PEF (LA-7) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0151] [Example 6] The substrate was a 25 μm-thick biaxially oriented PEF (BOPE-TEN) with a corona treatment surface. Heat-resistant coating agent 1 was applied at a coating rate of 0.5 g / cm. 3The corona-treated surface opposite the heat-resistant coating layer was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3 A polyethylene laminate of Example 6 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106° C., company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 70 μm-thick PEF (LA-7) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0152] [Example 7] The substrate was a biaxially oriented PEF (BOPE-TEN) with a thickness of 25 μm. The corona-treated surface was coated with heat-resistant coating agent 1 at a coating rate of 2.0 g / cm. 3 The corona-treated surface opposite the heat-resistant coating layer was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3 A polyethylene laminate of Example 7 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106° C., company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 100 μm-thick PEF (SK615P) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0153] [Example 8] The substrate was a biaxially oriented PEF (BOPE-TEN) with a thickness of 25 μm. The corona-treated surface was coated with heat-resistant coating agent 1 at a coating weight of 3.0 g / cm. 3The corona-treated surface opposite the heat-resistant coating layer was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3 A polyethylene laminate of Example 8 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106° C., company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 100 μm-thick PEF (SK615P) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0154] [Example 9] The corona-treated surface of the substrate (substrate 1) was a uniaxially stretched PEF with a thickness of 25 μm. Heat-resistant coating agent 1 was applied at a coating rate of 2.0 g / cm. 3 The corona-treated surface opposite the heat-resistant coating layer was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3 A polyethylene laminate of Example 9 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106° C., company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 100 μm-thick PEF (L-140R-1) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0155] [Example 10] The substrate was a biaxially oriented PEF (BOPE-TEN) with a thickness of 25 μm. The corona-treated surface was coated with heat-resistant coating agent 1 at a coating rate of 2.0 g / cm. 3The corona-treated surface opposite the heat-resistant coating layer was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3 A polyethylene laminate of Example 10 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106° C., company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 100 μm-thick PEF (L-535) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0156] [Example 11] The corona-treated surface of the substrate (substrate 1) was a uniaxially stretched PEF with a thickness of 25 μm. Heat-resistant coating agent 1 was applied at a coating rate of 2.0 g / cm. 3 The corona-treated surface opposite the heat-resistant coating layer was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3 A polyethylene laminate of Example 11 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106° C., company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 100 μm-thick PEF (L-535) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0157] [Example 12] The corona-treated surface of the substrate (substrate 2) was a uniaxially stretched PEF with a thickness of 25 μm. Heat-resistant coating agent 1 was applied at a coating rate of 2.0 g / cm. 3The corona-treated surface opposite the heat-resistant coating layer was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3 A polyethylene laminate of Example 12 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106° C., company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 100 μm-thick PEF (L-535) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0158] [Example 13] The corona-treated surface of the substrate (substrate 1) was a uniaxially stretched PEF with a thickness of 25 μm. Heat-resistant coating agent 1 was applied at a coating rate of 2.0 g / cm. 3 The corona-treated surface opposite the heat-resistant coating layer was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3 A polyethylene laminate of Example 13 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106° C., company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 30 μm-thick PEF (TUX-VCS) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0159] [Comparative Example 1] The corona-treated surface of the uniaxially oriented PEF (BOPE-TEN) substrate with a thickness of 25 μm was coated with a two-component curing polyurethane adhesive (A-3210 / A-3075, Mitsui Chemicals) to a thickness of 0.3 μm as an anchor coating agent, and then low-density polyethylene resin (density 0.918 g / cm) was applied to the coated surface. 3A polyethylene laminate of Comparative Example 1 was obtained by melt-extruding a polyethylene terephthalate (product name: Novatec LC600A, MFR: 7.0 g / 10 min, melting point: 106°C, company name: Japan Polyethylene Co., Ltd.) to a thickness of 15 μm while sandwiching a 70 μm-thick PEF (LA-7) as a sealant film. The obtained polyethylene laminate was used as a packaging material.

[0160] [Comparative Example 2] One side of a 100 μm thick sheet (grade: SK615P, Tamapoly Co., Ltd., additive-free PEF 100 μm thick) was corona-treated, and heat-resistant coating agent 1 was used, with a coating amount of 2.0 g / cm 3 The polyethylene film of Comparative Example 2 having the heat-resistant coating layer was used as a packaging material.

[0161] [Comparative Example 3] A polyethylene film having a thickness of 200 μm (PEF1) was used as the packaging material in Comparative Example 3.

[0162] [Physical property evaluation] The methods for evaluating the physical properties of packaging materials are described below. Unless otherwise specified, the environment during measurement of each physical property was a temperature of 23° C. and a humidity of 50% RH. Measurements were performed on three test pieces for each physical property, and the arithmetic mean value of the three values ​​obtained was recorded as the value of each physical property.

[0163] <Puncture strength> The puncture strength of the packaging material was measured in accordance with JIS Z1707:2019. The packaging material was cut to obtain a test piece having a width of 5 cm and a length of 5 cm. A Tensilon universal material testing machine RCT-1250A (manufactured by AND Co., Ltd.) was used as a measuring instrument. A semicircular needle having a diameter of 1.0 mm and a tip shape radius of 0.5 mm was pierced into the test piece at a test speed of 50 mm / min, and the maximum strength (N) until the needle penetrated the test piece was measured. In the case of a polyethylene laminate, the needle was pierced into the substrate surface to measure the puncture strength (N).

[0164] <Heat resistance evaluation> The Teflon sheet and the film samples of Examples 1 to 13 and Comparative Examples 1 to 3 were cut to 10 cm x 10 cm to obtain test pieces. The measurement device used was a heat seal tester TP-701 (manufactured by Tester Sangyo Co., Ltd.). The measurement conditions were a measurement temperature of 140°C to 190°C (in 10°C increments), a seal pressure of 0.1 MPa, and a seal time of 1 second. A Teflon sheet was placed on the substrate side of the sample, the seal was stepped on, and the heat resistance was evaluated for each measurement temperature according to the following criteria. (Judgment criteria) ○: The film sample was not attached to the Teflon sheet. △: The film sample was slightly taken up by the Teflon sheet. ×: The film sample was attached to the Teflon sheet.

[0165] <Metal concentration on film surface> A pouch (10×19 cm) was prepared for each film sample of Examples 1 to 13 and Comparative Examples 1 to 3. Next, impurities on the inner surface of the pouch were quantitatively analyzed by measuring with an ICP-MS (manufactured by Thermo Fisher Scientific) using a 3% by mass aqueous solution of nitric acid as the extraction solution. The elution of metal elements was evaluated according to the following criteria. (Judgment criteria) Verdict: Phosphorus (P) concentration: 50ppt or less Aluminum (Al) concentration: 10ppt or less The total of the six elements iron (Fe), chromium (Cr), nickel (Ni), copper (Cu), sodium (Na), and zinc (Zn) is 100 ppt or less. ×Verdict: Phosphorus (P) concentration: over 50ppt Aluminum (Al) concentration: over 10ppt The total of six elements, iron (Fe), chromium (Cr), nickel (Ni), copper (Cu), sodium (Na), and zinc (Zn), exceeds 100 ppt.

[0166] <Surface resistance value> The film samples of Examples 1 to 13 and Comparative Examples 1 to 3 were cut to 10 cm x 10 cm to obtain test pieces. The measurement device used was a Hiresta-UP MCP-HT450 (manufactured by Nitto Seiko Analytech Co., Ltd.). The measurement conditions were set to an applied voltage of 500 V and a timer of 30 seconds. The test piece was placed on the metal surface of a UFL register table and measured with a dedicated probe (URS).

[0167] <Evaluation of mechanical properties> The mechanical properties of the packaging material were evaluated using the above-mentioned puncture strength according to the following evaluation criteria. (Evaluation Criteria) ○:7N / 15mm width or more △: More than 5N / 15mm width, 7N / 15mm width or less ×:5N / 15mm width or less

[0168] <Recyclability evaluation> The polyethylene content of each of Examples 1 to 13 and Comparative Examples 1 to 3 was calculated and evaluated according to the following evaluation criteria. (Evaluation Criteria) ○: Polyethylene content is 80% by mass or more ×: Polyethylene content is less than 80% by mass

[0169] <Evaluation of bag making suitability> The bag-making suitability of the packaging material was evaluated according to the following evaluation criteria using the results of the heat resistance evaluation described above. (Evaluation Criteria) ○: Measurement temperature is 160℃ or higher. △: Measurement temperature 160℃ is judged as △ ×: Test temperature is 160℃ or higher.

[0170] [Table 1]

[0171] [Table 2] [Explanation of symbols]

[0172] 1 ...Laminate 10...Base material 20...adhesive layer 30…Sealant layer 40…Heat-resistant coating layer 50...Anchor coat layer

Claims

1. A packaging material comprising at least a heat-resistant coating layer, a substrate, an adhesive layer, and a sealant layer in this order, The substrate contains polyethylene as a main component, The sealant layer contains polyethylene as a main component, The total thickness is 150 μm or less. packaging materials.

2. 2. The packaging material according to claim 1, wherein the heat-resistant coating layer is a layer made of a cellulose acetate-based coating agent, a urethane-based coating agent, a polyvinyl chloride-based coating agent, or a polyvinyl chloride-vinyl acetate copolymer-based coating agent.

3. 2. The packaging material according to claim 1, wherein the substrate is an oriented substrate containing polyethylene as a main component.

4. 2. The packaging material according to claim 1, wherein the substrate is an oriented substrate containing high density polyethylene as a main component.

5. The packaging material of claim 1 , wherein the sealant layer is an unoriented layer.

6. The packaging material according to claim 1 , wherein the adhesive layer comprises an extruded resin layer containing polyethylene as a main component.

7. 2. The packaging material according to claim 1, wherein the content of polyethylene in the entire packaging material is 80% by mass or more.

8. The packaging material of claim 1 , wherein the packaging material is for industrial materials.

9. The packaging material of claim 8, wherein the industrial material is a semiconductor material.

10. A packaging bag comprising the packaging material according to any one of claims 1 to 9.

11. The packaging bag according to claim 10; Industrial materials contained in the packaging bag; A packaging body comprising:

12. The package of claim 11, wherein the industrial material is a semiconductor material.

Citation Information

Patent Citations

  • Shipping bag for silicon material and package body for silicon material

    JP2022122294A